Land Rights Registration for Indigenous Villages Towards a Sustainable Indigenous Village - I Nyoman Alit Puspadma (Journal Equity of Law and Governance, 2023)
This study aims to explore outcomes relating to the allocation of property rights to legal entities, with an emphasis on the importance of ministerial recommendations regarding such rights. This research utilizes a combined approach of normative and empirical research methods. Normative research methods were utilized to explore the legal and regulatory aspects related to the registration of land rights for indigenous villages, including an analysis of agrarian law, government regulations, and related policies governing the registration of such land rights. On the other hand, empirical research methods were conducted to collect field data related to the implementation of land rights registration for indigenous villages. Data collection was conducted through interviews with land rights certificate holders, direct observation of ngayah activities in indigenous villages, and analysis of the impact of land rights registration on the sustainability of indigenous villages. In the process of data analysis, various techniques were used, including in-depth analysis of agrarian law, government regulations and policies governing the registration of land rights for indigenous villages, in order to draw relevant conclusions. The results show that the allocation of property rights to legal entities has the potential to strengthen indigenous villages and achieve the goal of ajeg Bali. It is important for the government to ensure that these various factors are met in order for property rights to provide significant benefits to the viability and sustainability of the village.